Hubungan Tingkat Pengetahuan Dengan Kepatuhan Minum Obat Pasien Hipertensi Di Klinik Pratama Sukma Anggrek - Charles; Fachdiana; Adinda Rindy Puspita (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2025)
The level of knowledge and understanding of hypertensive patients regarding their disease can support the success of therapy so that the patient's blood pressure can be well controlled. Providing patients with knowledge and understanding of drug use and their disease will have an impact on treatment compliance and success in the healing process. The aim of this research is to determine the relationship between the level of knowledge and adherence to taking medication for hypertension patients at the Pratama Sukma Anggrek Clinic, Jatinegara Village, Jatinegara District, East Jakarta in the period April – May 2024. This research is a quantitative research with a correlation research design and uses a cross sectional approach. The sampling technique used in this research was a total sampling technique with a sample size equal to the population, namely 30 hypertensive patients. The data collection method used a questionnaire. The research results showed that the level of knowledge was less than 0%, sufficient knowledge was 70%, and good knowledge was 30%. The level of compliance in the less compliant category is 16.7%, compliance in the compliant category is 66.7%, and compliance in the highly compliant category is 16.7%. The statistical test in this study used the chi-square test. The results of the statistical test on knowledge of hypertension sufferers and adherence to taking medication showed p value = 0.04 < α= 0.05. partially there is a relationship between the level of knowledge and compliance with taking anti-hypertension medication at the Pratama Sukma Anggrek Clinic